Improvement on replication quality of electroformed nickel mold inserts with micro/nano-structures. (July 2016) - Weng, Can; Zhou, Mingyong; Jiang, Bingyan; Lv, Hui
Abstract: Electroforming has been successfully applied to transfer micro/nano-structures for fabrication of many highly precise products. Due to the difficulties of mass transfer within the micro/nano-cavities, the replication quality of micro/nano-structures is poor on the nickel electroformed mold inserts. In this paper, the effects of electrolyte convection on the flow field and nickel ion concentration distribution within the micro/nano-cavities have been investigated based on the COMSOL® Multiphysics software. Considering its micro/nano-hierarchical structures, a bamboo leaf has been applied as a master in the experiments. The surface appearances of mold inserts and the replication qualities of their micro/nano-structures have been greatly improved by enhancing the convection near the cathode.